Enhanced depth and location determination of conducting marine mines - Masoud Mahmoudi (2009)
Marine mines submerged in seawater or buried in beaches are a common danger in many areas of the world. The majority of marine mines are composed of metal and explosive materials. A novel scheme for detecting the location and depth of a metallic mine (modeled as a perfectly conducting sphere and spheroid) in marine environment is presented. This technique takes into account Eddy-Current Response (ECR) induced on the conducting marine mines as well as Current-Channeling Response (CCR) associated with the perturbation of currents induced in the conductive marine environment. It leverages on the unique electromotive force (EMF) induced in a receiving coil through different orientations of a transmitting coil with respect to the marine mine. Unlike conventional electromagnetic (EM) sensing apparatus which is used to carry out the measurement at just one attitude at a fixed angle with respect to buried mine, our proposed scheme consists of angular scanning via the symmetry axes of a concentric sensor over the metallic mine in order to obtain a unique normalized induced voltage determining the mine’s depth and location. Simulated results show that this technique has the potential of extending the depth of detection range up to 2 meters away from the sensor as well as enhancing the accuracy of detection in the conductive environment and sea water. The performance is superior to the current method available for the same application.